DISINTEGRATION OF COPPER ORES BY ELECTRIC PULSES - Kurytnik, I; Nussupbekov, B. R.; Khassenov, A. K.; Karabekova, D. Z. (POLSKA AKAD NAUK, 2015)
The article is concerned with methods of ragging and grinding of copper ore. The proposed electric pulse technology is one of the energetically favorable methods of ragging and grinding of natural minerals and anthropogenic raw materials. This paper presents optimal parameters in processing of the product. The results obtained by grinding of copper ore using the offered technology may be used under industrial conditions in the future.
Keywords: electric pulse technology; copper ore; reduction range